Master data management in practice : achieving true customer MDM - Cervo, Dalton, 1967- (Wiley corporate F & A series., 2011)
"Expert guidance for Master Data Management (MDM) implementation. Master Data Management in Practice provides a logical order toward planning, implementation, ongoing management, and advanced practices of Customer MDM with tables, graphs, and charts. Authors Dalton Cervo and Mark Allen show organizations how to implement Master Data Management (MDM) within their business model to create a more quality controlled approach for successfully managing and maintaining their customer master data. This book focuses on techniques that can improve data quality management, lower data maintenance costs, reduce corporate and compliance risks, and drive increased efficiency in customer data management practices. Designed for data management professionals and data management consulting firms. Addresses the aspects of defining the underlying scope, approach, architecture, and objectives necessary for the planning and execution of a Customer MDM initiative. Provides the practical insight, guidance, questions, and examples related to the implementation of the four foundational Customer MDM disciplines: Data Governance, Data Stewardship, Data Quality Management, and Data Access Management. Packed with helpful tables, graphs, and charts, Master Data Management in Practice discusses current concepts and future implications associated to Customer MDM, revealing a logical order toward the planning, implementation, and ongoing management of solid Customer MDM practices. Praise for Master Data Management in Practice: Achieving True Customer MDM. "As more and more companies recognize the benefits of customer master data management (MDM), they are also learning that effective customer MDM requires careful planning and execution. Responding to the growing demand for tried and true knowledge on how to successfully implement and manage customer MDM practices, this book from Dalton Cervo and Mark Allen delivers very insightful and practical hands-on techniques from both the program manager and data steward points of view. It should be at the top of the 'must read' list for anyone looking to implement a customer MDM initiative."--Ron Powell, BeyeNETWORK Associate Publisher/Editorial Director TechTarget Enterprise Applications Group. "Organizations today are awash in a sea of structured and unstructured data, often lacking the tools, framework, and human resources to effectively manage their most valuable resource. In MDM in Practice, Cervo and Allen knock the ball out of the park. Rife with practical lessons, this how-to guide is essential reading for those determined to maximize the value of their information and avoid mistakes made far too frequently."--Phil Simon, author, The New Small and The Next Wave of Technologies. "Master data management is often neglected yet is a critical asset for any business. Cervo and Allen bring a new and refreshing hands-on perspective to a complex and, often, hard to manage customer data domain. Their experience and practical wisdom of the issues are compelling and unrivaled."--Peter Jaumann, Director, Customer Analytics and Insights, HP. "Dalton Cervo and Mark Allen demystify the theories and industry buzz surrounding Master Data Management (MDM), and provide a practical guide for successfully implementing a Customer MDM program, which includes discussing the three major types of MDM (Analytical, Operational, and Enterprise) as well as explaining exactly how MDM is related to, and supported by, Data Governance, Data Stewardship, and Data Quality. Dalton and Mark explain how MDM does much more than just bring data together--it provides a set of processes, services, and policies that bring people together in a cross-functional and collaborative approach to enterprise data management, where people, empowered by high quality data and enabled by technology, can optimize business processes for superior business performance."--Jim Harris, independent consultant, speaker, and freelance writer, as well as the Blogger-in-Chief at Obsessive-Compulsive Data Quality (www.ocdqblog.com). "This publication, by two of the most experienced practitioners in the field of Master Data Management (MDM), provides clear direction for any organisation looking to navigate their way through the complex challenges posed by Customer MDM. One of the questions we regularly get asked by readers is 'Where do we start with MDM?' In this book they will find not only the solution to creating buy-in and successfully launching an initiative, but more importantly, maturing MDM for the long-haul with sound data governance, data quality and change management techniques."--Dylan Jones, Founder of Data Quality Pro, an expert online resource for data quality professionals. "Dalton's and Mark's book provides some practical advice for those looking to implement a customer data integration program. They have clearly done a great job at abstracting good master data management practices in a succinct yet approachable way. Another great addition to the field!"--David Loshin, President, Knowledge Integrity Incorporated, Inc. "This book provides a very practical guide to understanding and implementing Customer Master Data Management. Dalton and Mark draw from their experience in actual implementations to provide insights and best practices that can be used by the most experienced implementers. At the same time, it offers a clear background and foundation on MDM to those that are just getting started."--Tony Fisher, President and CEO, DataFlux"--